Living With Multiple Sclerosis: The Rainbow of Inspiring Experiences and Resilience in the Face of the Disease - Leily Zare; Nahid Dehghan Nayeri; Fatemeh Bahramnezhad; Arezoo Rasti (Wiley, 2024)
ABSTRACT Introduction Multiple sclerosis (MS), a leading cause of disability in young adults worldwide, including in Iran, affects their whole life so common care is no longer effective. In this regard, context‐based approaches should be considered for a holistic care delivery that accords with the patients' inputs. We aimed to explore patients' understanding of MS and their personal experiences of living with this disease. Methods A qualitative descriptive study was conducted. The data were collected through in‐depth, semi‐structured interviews with 17 patients. These patients were selected using a purposive sampling method, and the data were analyzed using a conventional content analysis approach. Findings Three main categories and nine subcategories were identified: Thunder and Lightning strike in the form of Displeasure, Social wrong beliefs, Experiences of Constraints, Interference with Life Stages and Dark Spots on the Horizon of the Future; Subtle Beam consisting of Extrinsic Light Radiation, Reflection of Individual Effort and Formation of a Rainbow by Resilience and Hope for a Bright Future. Conclusion By offering multidimensional support, patients reported a shift from fear to a vibrant life. Although research often focuses on the negative aspects of MS, this study recognizes both positive and negative aspects. These findings can contribute to future interventional research. Patient or Public Contribution During the explanation of research goals and consent acquisition, participants were reminded that sharing their experiences could provide valuable insights benefiting others coping with or at risk of the same disease. Additionally, during data analysis, codes extracted were reviewed and improved with active participant involvement.